Magnitude and Mechanism of Siderophore-Mediated Competition at Low Iron Solubility in the Pseudomonas aeruginosa Pyochelin System - Schiessl, Konstanze T.; Janssen, Elisabeth M.-L.; Kraemer, Stephan M.; McNeill, Kristopher; Ackermann, Martin (Frontiers in Microbiology, 2017)
A central question in microbial ecology is whether microbial interactions are predominantly cooperative or competitive. The secretion of siderophores, microbial iron chelators, is a model system for cooperative interactions. However, siderophores have also been shown to mediate competition by sequestering available iron and making it unavailable to competitors. The details of how siderophores mediate competition are not well understood, especially considering the complex distribution of iron phases in the environment. One pertinent question is whether sequestering iron through siderophores can indeed be effective in natural conditions; many natural environments are characterized by large pools of precipitated iron, and it is conceivable that any soluble iron that is sequestered by siderophores is replenished by the dissolution of these precipitated iron sources. Our goal here was to address this issue, and investigate the magnitude and mechanism of siderophore-mediated competition in the presence of precipitated iron. We combined experimental work with thermodynamic modeling, using Pseudomonas aeruginosa as a model system and ferrihydrite precipitates as the iron source with low solubility. Our experiments show that competitive growth inhibition by the siderophore pyochelin is indeed efficient, and that inhibition of a competitor can even have a stronger growth-promoting effect than solubilization of precipitated iron. Based on the results of our thermodynamic models we conclude that the observed inhibition of a competitor is effective because sequestered iron is only very slowly replenished by the dissolution of precipitated iron. Our research highlights the importance of competitive benefits mediated by siderophores, and underlines that the dynamics of siderophore production and uptake in environmental communities could be a signature of competitive, not just cooperative, dynamics.